Ethics and Aesthetics for Enhancing Design and Transforming Social Reality - Batista, Miguel Angel Herrera; Alvarez, Marco Antonio Marin; Alvarez, Carlos Angulo (Journal of Leadership, Accountability and Ethics, 2022)
Design is preponderant in the world economy; it allows competition and enhances the development of innovations in the market. The expansion of product offerings provides options to satisfy the user’s needs, which is an undeniable advance driven by design. However, this has led to a significant increase in the production of solid waste related to design, which generates environmental deterioration. Additionally, the supply of design products has been concentrated in the most economically favored sector, leaving out a large part of the world’s population which are not met because they are not a market of interest for the productive industry in general. The content of this paper is the result of a collective debate from the authors, based on the analysis of documentary sources and their own experience as academics. Our objective is to encourage discussion for the creation of a common front oriented towards a design practice focused simultaneously on social development and environmental care; a design practice based on ethics and commitment to the environment and society.